ANALISIS PENERAPAN BLUE OCEAN STRATEGY BAGI INDUSTRI KERAJINAN DI KOTA TANJUNG REDEB: ANALISIS PENERAPAN BLUE OCEAN STRATEGY BAGI INDUSTRI KERAJINAN DI KOTA TANJUNG REDEB - Muhammad Amin (ECO-BUILD, 2025)
This research is to find out and analyze the Blue Oceans Strategy approach to improve strategy development for the Small and Medium Enterprises of Shell Crafts. The data processing and analysis method used is through a postpositivism research approach, namely qualitative research. Qualitative analysis consists of the eliminate-reduce-increase-create scheme, strategy canvas and blue ocean index at IKM Seashell Crafts in Tanjung Redeb. Meanwhile, the quantitative analysis used consisted of the Cochran test, performance appraisal test, and factor analysis. The results of the study show that a comparative analysis in the application of red ocean strategy and blue ocean strategy is seen using the eliminate-reduce-increase-create scheme, strategy canvas and blue ocean index.